Efficacy of ultrasound treatment in the removal of pesticide residues from fresh vegetables: A review. (March 2020) - Azam, S M Roknul; Ma, Haile; Xu, Baoguo; Devi, Shoma; Siddique, Md Abu Bakar; Stanley, Sarah L.; Bhandari, Bhesh; Zhu, Junsong
Abstract: Background: Pesticide residues (PR) present in food are potentially toxic components to humans and can be the cause of severe health problems, depending on the means and amounts of individual exposure. Among the different routes of pesticide exposure, the most likely exposure is through the direct consumption of fresh foods. Scope and approach: To remove PR from fresh agricultural products and improve food safety for consumers, various pesticide removal methods have been studied in recent decades. Several cleaning techniques such as usage of surfactants, ozone (O3 ), ionic solvent, and chlorine treatment have been applied to reduce the presence of pesticides. However, none of these methods have been reported as being successful in removing PR without any physical or chemical side effects to the food itself. Therefore, there is a crucial need for investigation of more effective, sustainable, and environment-friendly pest and pesticide removal practices. Key findings and conclusions: Ultrasound-assisted cleaning (UAC) is considered to be an environment-friendly and effective pesticide eliminating process which is unique in its ability to remove the contaminants compared to conventional methods. It is also a time and energy-saving method of cleaning. This review gathers and focuses on the most relevant works on the UAC techniques of organic or inorganic pesticides applied during the growth of fresh vegetables, which are mostly eaten raw or after minimal processing. The findings of the reviewed works suggest that ultrasonication itself would be beneficial as a vegetable-cleaning technology, or could be readily combined with another suitable method. Highlights: Commonly used pesticides in fresh vegetables and their residual effects are studied. Ultrasound-assisted cleaning and conventional pesticide removing methods are reviewed. The efficacy of ultrasound sanitizing in the removal of pesticide residue is summarized. Conceivable ways of achieving synergism effects are recommended. Scopes and limitations of ultrasonication in removing pesticides are outlined.